A musicoterapia na preservação da memória e na qualidade de vida de idosos institucionalizados - Medeiros, Ivany Fabiano (2013)
In the aging process, the subjects suffer several physical mental and psychological transformations, aside the social reaction to old age. The population growth of aged persons is made clear with statatisics from the United Nations(UN); confronted with this inevitable amount of old people, it becomes necessary to integrate one to maintenance/improval of his quality of life, considering specially those institutionalized. Musical therapy can act as one type of treatment, aiming his rehabilitations and/or preservation of his cognitive functions. This work, of quali-quantitive nature, has as primary objective of investigating the contributions of Musical therapy for the preservation of memory and quality of life for institutionalizes aged people. There was an experimental research conducted in a home for the elderly at Goiânia, with a closed group of six people, with ages between 65 and 75. The musical therapeutical interventions were applied for a period of four months, resulting in sixteen weekly sessions sixty minutes each. Before and after the interventions the tests WHOQOLBREF (The World Health Organization Instrument to Evaluate Quality of Life Bref), WHOQOL-OLD OLD (The World Health Organization Instrument to Evaluate Quality of Life Old) and MINIMENTAL (Mini Exam of the State of Mind) were applied. During the interventions there were categories established that evaluated the memory during the whole process. At the end of the therapeutical procedure, a final interview was conducted. As to the results gained, it was possible to observe that through the application of the MIIMENTAL, there were memory, writing, drawing and calculation improvements, while the other functions were preserved. In the test that evaluated quality of life WHOQOL-BREF there were trends pointing to the improval on the physical, psychological and environmental categories. In the WHOQOL-OLD there were perspectives to improve in the following dimensions: sensory, autonomy, social, death and intimacy. Both tests did not present statistical relevance. Through the musical experiences (BRUSCIA, 2000) the elderly have had the opportunity to recall their reminisces and the closure to express their emotions. The Music therapy has enabled the preservation of cognitive functions specially in the long term memory, the semantical memory and the episodical memory. In face with the satisfactory results obtained in this research, it is believed in music therapy as an intervention that preserves the quality of life of institutionalized elders.